Factors associated with sedentary lifestyle in higher education young students. Peru, 2017 - Navarrete Mejia, Pedro Javier (2019)
Objective: To determine the variables associated with sedentary lifestyle in young students of a public institution of higher education in Lima-Peru. Materials and methods: An observational, cross-sectional, analytical, retrospective study. Data was collected from the students’ medical evaluation form and academic records. The sample consisted of 187 higher education students. Variables such as age, sex, weight, height, abdominal perimeter, academic term, academic performance and academic program were assessed. The students’ annual medical evaluation included answering the International Physical Activity Questionnaire (IPAQ). For the identification of the variables associated with sedentary lifestyle, the chi square-test was used. A significance level of 95 % was accepted (p <0.05). Results: The average age was 18.6 years (CI 16.9 - 20.3), 80 % were male, 39 % were obese/overweight, 12 % had abdominal obesity, 32 % were attending the nursing program, and 73.8 % had a moderate or low academic performance. A sedentary lifestyle was determined in 65.8 % of the cases. Sedentary students had on average 242.17 MET min/week, while students with physical activity achieved 5371.13 MET min/week. A statistically significant association of sedentary lifestyle with overweight/obesity (p = 0.023), abdominal obesity (p = 0.048), moderate academic performance (p = 0.012), and the Computer Science Academic Program (p = 0.036) was evidenced. Conclusions: There is a high level of sedentary lifestyle in the evaluated students, ignoring the recommendations of the World Health Organization (WHO) on physical activity (≥600 EMT min/week). The nutritional status of overweight/obesity and moderate academic performance were significantly associated with a sedentary lifestyle.